2000
DOI: 10.2134/jeq2000.00472425002900020020x
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Water Quality from Poultry Litter‐Treated Pasture and Forest Sites

Abstract: In the Ozark Highlands of the USA (36–38° N, 91–95° W), annual application of poultry litter to pasture land is a routine waste management practice. The objective of this study was to measure the effect of site characteristics and poultry litter application on runoff and nutrient transport from grazed pasture and forest sites at different landscape positions. Sixteen pairs of 1 × 2 m plots were established on Nixa (loamy‐skeletal, siliceous, active, mesic Glossic Fragiudults) and Clarksville (loamy‐skeletal, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 0 publications
9
73
0
2
Order By: Relevance
“…The total P content in the poultry litter ranged from 13.7 to 18.1 g kg -1 , with a higher P content and consequently lower N/P ratio in the CC than in the other litters. The average C and N content of the litters were 446 and 33 g kg -1 , respectively, similar to the values reported elsewhere (Kingery et al, 1994;Williams et al, 1999;Sauer et al, 2000), except that the P content was considerably higher in our study. There was no significant difference in the total C, N and C/N ratio among the litters.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The total P content in the poultry litter ranged from 13.7 to 18.1 g kg -1 , with a higher P content and consequently lower N/P ratio in the CC than in the other litters. The average C and N content of the litters were 446 and 33 g kg -1 , respectively, similar to the values reported elsewhere (Kingery et al, 1994;Williams et al, 1999;Sauer et al, 2000), except that the P content was considerably higher in our study. There was no significant difference in the total C, N and C/N ratio among the litters.…”
Section: Resultssupporting
confidence: 92%
“…The total production of swine and poultry manure in Brazil was estimated at 65 million tons, based on the number of swine and poultry animals in 2003 (IBGE, 2003), and since then this number has increased tremendously. This material generally contains high levels of plant macronutrients, ranging from 39 to 49 g kg -1 N, 3.6 to 9.9 g kg -1 P, and 10 to 20 g kg -1 K (Kingery et al, 1994;Williams et al, 1999;Sauer et al, 2000). Poultry litters in the Zona da Mata in Minas Gerais contain on average 34 g kg -1 N, 16 g kg -1 R. Bras.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the relationship between manure application and P concentrations in surface runoff Shreve et al, 1995;Sauer et al, 2000;Wood et al, 1999).…”
Section: Effects Of Poultry Manure Treatments On Po4-p Concentrationsmentioning
confidence: 99%
“…Previous research has suggested that concentrations of total P in runoff are highly correlated with plant-available P in the surface soil (Sharpley 1995;Pote et al 1996;Sauer et al 2000). In the current study, the relationships were statistically significant, but weak, regardless of grazing treatment or grazing year (Fig.…”
Section: Regressions Predicting Infiltration Rate Surface Runoff Andmentioning
confidence: 99%